The Role of the Lawyer in the Administrative Lawsuit: A Comparative Study - Atshsn, Nassrullah (Journal of Legal Sciences, 2023)
The legislators in (France, Egypt and Syria) set controls for filing an administrative lawsuit, including the signature of the lawsuit petition by a lawyer accepted before the court, and the lawyer is committed to performing his work in accordance with the conditions of the State Council and the practice of the legal profession. And if the goal of the legislator is to achieve the public and private interest represented in observing the law and assisting the plaintiff legally, then this condition sometimes leads to individuals refraining from resorting to the judiciary because of the financial cost of registration fees and lawyers, which prompted the legislator, especially the French, to exempt several lawsuits from this condition, including lawsuits for annulment Allowing the plaintiff to submit the petition himself, even without paying the fee in advance, to prevent the administration from abuse of its powers, and this was not taken into account by the legislators in Egypt and Syria, despite their stipulation that some lawsuits be excluded from this condition. The law of the State Council in these countries stipulates that the State Commissioners Authority undertake the preparation of the case, and the commissioner undertakes all the work to prepare the case for ruling on it, and organizes a draft ruling that the judge often adopts, especially in France, in addition to the positive role of the judge, which allows legislation to mitigate this condition .